Application of Statistical Quality Control Methods to Sarong Product Quality at UD. Utomo Joyo - Ahmad Watsiqul Syukri; Moh. Jufriyanto; Akhmad Wasiur Rizqi (Fakultas Teknik, 2023)
UD. Utomo Joyo has problems related to monthly production defects, where the company has a maximum defect target of 5% of total production for one period, but the defects that occur exceed estimates. This study aims to find solutions to improve the application of the Statistical Quality Control method to the quality of sarong products at UD. Utomo Joyo using Seven Quality Control Tools (7 QC), namely flowcharts, checksheets, histograms, control charts, pareto diagrams, scatter diagrams, and fishbone diagrams. The results of the analysis and discussion show that there are 2 types of product defects such as yarn break defects and color fade/flex defects, while the most common or dominant defect is yarn break defects with a percentage of 68.3%. The findings of these defective products are still within the control limits of UCL and LCL. The proposed improvements are rescheduling to check tools regularly, providing adequate and safe lighting facilities for eye health, providing SOP education to workers before starting work. The advice given is to provide more focus on the most common or dominant product defects, in order to reduce losses and increase customer satisfaction in the future.